Magnetized hydrophobic chitosan-alum composite flocculant as well as preparation method and application thereof

By modifying chitosan to hydrophobicity and compounding with alum, and then adding Fe3O4 magnetic particles to form a magnetized hydrophobic chitosan-alum composite flocculant, the problem of low microplastic removal rate in the prior art is solved, and an efficient and reusable microplastic removal effect is achieved.

CN119841412AActive Publication Date: 2025-04-18HAINAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510188742.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-18
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

When treating microplastics in wastewater, the existing hydrophobic chitosan has low removal rate and has problems such as high solubility, low mechanical strength, poor reusability and weak separation ability.

Method used

A magnetized hydrophobic chitosan-alum composite flocculant was designed. By modifying chitosan to hydrophobicity, compounding it with alum, and adding Fe3O4 magnetic particles to form a magnetized hydrophobic chitosan-alum composite flocculant.

Benefits of technology

The removal rate of different types of microplastics is significantly improved, the removal effect is effective within a wide pH range, and it can achieve high removal rate at a smaller dose, and is recovered through an external magnetic field, reducing the residue of flocculant in wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841412A_ABST
    Figure CN119841412A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a magnetized hydrophobic chitosan-alum composite flocculant, which comprises the following steps: mixing chitosan with lauric acid, N-hydroxysuccinimide (NHS) and 1-ethyl (3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) to obtain hydrophobic chitosan; then hydrophobic chitosan and Fe3O4 magnetic particles are mixed to obtain magnetized hydrophobic chitosan, and then the magnetized hydrophobic chitosan reacts with Al2 (SO4) 3.18 H2O and K2SO4 to prepare the magnetized hydrophobic chitosan-alum composite flocculant. The magnetized hydrophobic chitosan-alum composite flocculant prepared by the invention has the advantages of better stability in sewage, small dosage, high removal rate and better settleability, and can be recycled and removed through an external magnetic field, so that the residual quantity of the flocculant in the treated wastewater is small, and secondary pollution is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of water treatment, and in particular to a magnetized hydrophobic chitosan-alum composite flocculant and a preparation method and application thereof. Background Art

[0002] Plastics are widely used in modern life because of their good performance and low cost. Plastic waste will gradually degrade into microplastics (MPs) in the natural environment. Microplastics are plastic particles less than 5 mm in size. Microplastics have a large specific surface area. Aged and broken microplastics have rich functional groups. During the migration and transformation process, they have an enrichment effect on heavy metals, organic pollutants, pathogens, etc., thus constituting complex pollution. Therefore, the pollution control of microplastics in water bodies is imminent.

[0003] At present, the commonly used treatment method for removing microplastics from wastewater is chemical coagulation, which is to add flocculants to wastewater to make suspended particles or colloids in the water condense to produce floccules, and then separate the floccules from the wastewater to remove pollutants and purify the wastewater. Chemical coagulation is an economical, practical, easy-to-operate and effective sewage treatment technology. It is widely used in the water treatment industry and occupies an important position in wastewater treatment.

[0004] The key to treating wastewater by chemical coagulation is to select a suitable flocculant. Studies have shown that the use of natural flocculants shows good results in MPs removal and has many advantages over traditional flocculants (inorganic flocculants and organic flocculants).

[0005] Chitosan is a natural flocculant with many active functional groups on its molecular chain that can form hydrophobic associations and complexes with pollutants in water bodies. It also has good biocompatibility and biodegradability. Chitosan has been proven to be one of the most effective and environmentally friendly products in the coagulation process. However, chitosan is hydrophilic, while microplastics are hydrophobic. Simply using chitosan as a flocculant will not have a strong removal ability.

[0006] At present, in the relevant technology, CS can be modified into hydrophobic chitosan to improve the removal ability of hydrophobic microplastic pollutants, but the overall removal effect is not obvious, the removal rate is not high, and the hydrophobic chitosan is powdery. In an acidic environment, it has high solubility, low mechanical strength, poor reusability, and weak separation ability. Therefore, in order to solve these problems, a new type of composite flocculant is designed for hydrophobic microplastic pollutants, so as to better adapt to water bodies containing hydrophobic microplastic pollutants and improve the removal rate of microplastics. Summary of the invention

[0007] Therefore, the purpose of the present invention is to provide a magnetized hydrophobic chitosan-alum composite flocculant and its preparation method and application, so as to solve the above-mentioned problems that the current hydrophobic chitosan has an insufficient overall removal rate when treating microplastic pollutants in sewage, and has high solubility, low mechanical strength, poor reusability, and strong separation ability.

[0008] The first aspect of the present invention is to provide a method for preparing a magnetized hydrophobic chitosan-alum composite flocculant, the preparation method comprising the following steps:

[0009] (1) dissolving chitosan in acetic acid to obtain a chitosan solution, adding methanol to the chitosan solution, adjusting the pH of the solution after stirring, and obtaining an acidified chitosan solution;

[0010] (2) preparing mother solutions of lauric acid, N-hydroxysuccinimide (NHS), and 1-ethyl (3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) respectively, taking solutions of lauric acid, N-hydroxysuccinimide (NHS), and 1-ethyl (3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) respectively, adding them to ethanol simultaneously and stirring, adding acidified chitosan solution during stirring to react, adjusting the pH of the reaction solution after the reaction, and obtaining hydrophobic chitosan powder by centrifugation, washing, drying, and grinding;

[0011] (3) adding hydrophobic chitosan powder into water, stirring, and then adding Fe3O4 magnetic particles to mix to obtain a mixed solution, first adding cyclohexane, an emulsifier, and a surfactant into the mixed solution, stirring and mixing, and then adding glutaraldehyde to carry out a cross-linking reaction to obtain a magnetized hydrophobic chitosan solution, collecting the magnetized hydrophobic chitosan solution through an external magnetic field, and washing, drying, and grinding to obtain a magnetized hydrophobic chitosan powder;

[0012] (4) dissolving the obtained magnetized hydrophobic chitosan powder in an acetic acid solution or a hydrochloric acid solution to obtain a magnetized hydrophobic chitosan solution, adding Al2(SO4)3·18H2O and K2SO4 to the magnetized hydrophobic chitosan solution for reaction, and allowing to stand and mature after the reaction to obtain a magnetized hydrophobic chitosan-alum composite flocculant.

[0013] In an optional embodiment, in the above step (2), the molar ratio of chitosan to lauric acid is 1:(0.2-2).

[0014] In an optional embodiment, in the above step (2), the molar ratio of lauric acid, N-hydroxysuccinimide (NHS), and 1-ethyl (3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) is 1:2:2.

[0015] In an optional embodiment, in the above step (3), the mass ratio of hydrophobic chitosan powder to Fe3O4 magnetic particles is 1:(0.5-3).

[0016] In an optional embodiment, in the above step (3), the volume ratio of cyclohexane, emulsifier and surfactant is 150:1:30.

[0017] In an optional embodiment, in the above step (4), the mass ratio of Al2(SO4)3·18H2O to K2SO4 is 1:(1-4).

[0018] In an optional embodiment, in the above step (1), before adding methanol to the chitosan solution, the chitosan solution is first placed in a storage box at 2 to 6° C. for 24 to 28 hours, and the pH of the chitosan solution is adjusted by 1% acetic acid, and the pH of the acidified chitosan solution is 4;

[0019] In the step (2), lauric acid, N-hydroxysuccinimide (NHS), and 1-ethyl (3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) are added to ethanol and stirred for 2 to 4 hours, and the acidified chitosan solution is added for reaction for 24 to 28 hours. The reaction solution is first ultrasonicated for 10 to 15 minutes and then the pH value of the reaction solution is adjusted to 9. The reaction solution is then placed in a storage box at 2 to 6° C. and stored for 24 to 28 hours. The hydrophobic chitosan powder is then obtained by centrifugation, washing, drying, and grinding.

[0020] In an optional embodiment, in the above step (3), the hydrophobic chitosan and the Fe3O4 magnetic particles are mixed for 12 to 15 hours, cyclohexane, emulsifier and surfactant are added to the mixture for stirring and mixing for 3 to 5 hours, glutaraldehyde is added for cross-linking reaction at 50°C for 3 to 5 hours, and the drying time is 24 to 26 hours;

[0021] In the step (4), Al2(SO4)3·18H2O and K2SO4 are added to the magnetized hydrophobic chitosan solution at a temperature of 50 to 80°C, and the reaction is carried out at a rotation speed of 600 to 750 r / min for 3 to 5 hours, and the standing and aging time is 24 to 28 hours.

[0022] The second aspect of the present invention is to provide a magnetic hydrophobic chitosan-alum composite flocculant prepared by the above-mentioned preparation method.

[0023] The third aspect of the present invention is to provide an application of a magnetized hydrophobic chitosan-alum composite flocculant in the treatment of wastewater containing microplastics.

[0024] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0025] (1) The removal rates of the present invention for different types of microplastics, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), and polylactic acid (PLA), are 99.85%, 99.55%, 99.05%, and 99.60%, respectively, with good removal effects.

[0026] (2) The present invention has a significant removal effect on different types of microplastics such as polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), and polylactic acid (PLA), and can effectively remove them within a wide pH range (pH range of 5 to 10), and can significantly shorten the reaction time of the flocculant.

[0027] (3) The present invention has good stability in sewage, small dosage, high removal rate, and can also be recovered and removed through an external magnetic field, so that the residual amount of flocculant in the treated wastewater is small and there is no secondary pollution.

[0028] (4) The present invention is applicable to a wide range of sewage temperature and can effectively remove microplastics in sewage at a temperature of 10 to 40°C. It is suitable for sewage treatment plants and natural water bodies and has good application prospects.

[0029] (5) The hydrolyzate produced by the hydrolysis of alum in the composite flocculant of the present invention can sweep away pollutants, so that the flocs can be quickly separated from the water and settled under the action of gravity, and the settling performance is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is an infrared analysis chart of the magnetized hydrophobic chitosan-alum composite flocculant prepared in Example 1 of the present invention, wherein the abscissa: wave number; the ordinate: transmittance.

[0031] Figure 2 The contact angles of the magnetized hydrophobic chitosan-alum composite flocculants prepared by using chitosan and lauric acid in different molar ratios according to the embodiments of the present invention; wherein, the horizontal axis is the molar ratio of chitosan to lauric acid; and the vertical axis is the removal rate.

[0032] Figure 3 This is a diagram showing the removal effect of PE by the magnetized hydrophobic chitosan-alum composite flocculant prepared by using different mass ratios of Al2(SO4)3·18H2O and K2SO4 in an embodiment of the present invention, wherein the horizontal axis is the mass ratio of Al2(SO4)3·18H2O to K2SO4; the vertical axis is the removal rate.

[0033] Figure 4This is a diagram showing the removal effects of different dosages of the magnetized hydrophobic chitosan-alum composite flocculant prepared in an embodiment of the present invention on PE, PET, PP, and PLA, wherein the horizontal axis is dosage; the vertical axis is removal rate.

[0034] Figure 5 This is a diagram showing the removal effect of the magnetized hydrophobic chitosan-alum composite flocculant prepared in an embodiment of the present invention on PE, PET, PP, and PLA at different temperatures; the horizontal axis: temperature; the vertical axis: removal rate.

[0035] Figure 6 This is a diagram showing the removal effect of the magnetized hydrophobic chitosan-alum composite flocculant prepared in an embodiment of the present invention on PE, PET, PP, and PLA at different pH values; abscissa: pH; ordinate: removal rate.

[0036] Figure 7 The figure is a diagram showing the removal effect of PE by flocculants prepared by adding different amounts of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4; the horizontal axis is the amount of addition; the vertical axis is the removal rate.

[0037] Figure 8 This is a diagram showing the removal effect of PE at different dosages of different composite flocculants; horizontal axis: dosage; vertical axis: removal rate. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0039] Example 1

[0040] A method for preparing a magnetized hydrophobic chitosan-alum composite flocculant comprises the following steps:

[0041] (1) 1.2 g of chitosan (deacetylation degree ≥ 95%, molecular weight: 30,000) was dissolved in 100 mL of 1% acetic acid, and the chitosan solution was stored at 4° C. for 24 h.

[0042] (2) 100 mL of methanol was added to the chitosan solution of step (1) and stirred for 10 min. The pH of the solution was adjusted to 4 with 1% (v / v) acetic acid and then ultrasonicated for 10 min to obtain an acidified chitosan solution.

[0043] (3) Prepare mother solutions of lauric acid, N-hydroxysuccinimide (NHS), and 1-ethyl (3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) with a concentration of 0.1 g / mL, add 20 μmol (4.01 mg) of lauric acid, 40 μmol (4.60 mg) of NHS, and 40 μmol (7.67 mg) of EDC to 10 mL of ethanol and stir for 2 h. Then, add the mixture to the acidified chitosan solution of step (2) and react for 24 h under stirring.

[0044] (4) After ultrasonicating the reaction solution of step (3) for 10 min, the pH of the reaction solution was adjusted to 9 using 2 mol / L NaOH solution, and the solution was finally stored at 4° C. for 24 h.

[0045] (5) The solution of step (4) was centrifuged at 5000 r / min, and the precipitate was washed with deionized water for 3 times to remove residual NaOH and unreacted lauric acid, EDC and NHS, and then dried and ground to obtain hydrophobic chitosan powder.

[0046] (6) 1.2 g of the hydrophobic chitosan powder obtained in step (5) was added to deionized water to prepare 30 mL of a 4.0 wt% hydrophobic chitosan solution, which was mixed with 1.2 g of Fe3O4 magnetic particles for 12 h to obtain a mixed solution.

[0047] (7) The mixed solution obtained in step (6) was stirred with 150 mL of cyclohexane and 1 mL of emulsifier span-80 in a three-necked flask for 3 h at a stirring speed of 250 r / min, and then 0.75 mL of glutaraldehyde was added for cross-linking reaction at a temperature of 50° C. and a speed of 250 r / min for 3 h to obtain a magnetized hydrophobic chitosan solution.

[0048] (8) The magnetized hydrophobic chitosan solution obtained in step (7) is collected by an external magnetic field, washed with anhydrous ethanol for several times to remove excess chemical reagents, and dried for 24 hours to obtain magnetized hydrophobic chitosan powder.

[0049] (9) weighing 1.0 g of the magnetized hydrophobic chitosan powder obtained in step (8) and dissolving it in 100 mL of 1% acetic acid solution to obtain a magnetized hydrophobic chitosan solution;

[0050] (10) At a temperature of 70° C. and a rotation speed of 250 r / min, 0.7 g of Al2(SO4)3·18H2O and 2.1 g of K2SO4 were added to the magnetized hydrophobic chitosan solution obtained in step (9), and the mixture was reacted at a rotation speed of 650 r / min for 3 h. After the reaction, the mixture was allowed to stand and mature for 24 h to obtain a magnetized hydrophobic chitosan-alum composite flocculant.

[0051] like Figure 1As shown, this is the infrared analysis diagram of the magnetized hydrophobic chitosan-alum composite flocculant prepared in Example 1.

[0052] Example 2

[0053] The preparation method of this embodiment is the same as that of embodiment 1, except that the mass of lauric acid in step (2) is different. In this embodiment, the mass of lauric acid is adjusted to 1.60 mg (8 μmol), and the rest remains unchanged.

[0054] Example 3

[0055] The preparation method of this embodiment is the same as that of embodiment 1, except that the mass of lauric acid in step (2) is different. In this embodiment, the mass of lauric acid is adjusted to 8.01 mg (40 μmol), and the rest remains unchanged.

[0056] Example 4

[0057] The preparation method of this embodiment is the same as that of embodiment 1, except that the mass of lauric acid in step (2) is different. In this embodiment, the mass of lauric acid is adjusted to 16.03 mg (80 μmol), and the rest remains unchanged.

[0058] Example 5

[0059] The preparation method of this embodiment is the same as that of embodiment 1, except that the mass of K2SO4 added in step (10) is different. In this embodiment, the mass of K2SO4 is adjusted to 0.7 g, and the rest remains unchanged.

[0060] Example 6

[0061] The preparation method of this embodiment is the same as that of embodiment 1, except that the mass of K2SO4 added in step (10) is different. In this embodiment, the mass of K2SO4 is adjusted to 1.4 g, and the rest remains unchanged.

[0062] Example 7

[0063] The preparation method of this embodiment is the same as that of embodiment 1, except that the mass of K2SO4 added in step (10) is different. In this embodiment, the mass of K2SO4 is adjusted to 2.8 g, and the rest remains unchanged.

[0064] Comparative Example 1

[0065] A method for preparing a hydrophobic chitosan flocculant is the same as steps (1) to (5) in Example 1. After obtaining the hydrophobic chitosan powder in step (5), the hydrophobic chitosan powder is made into a solution and then left to stand and mature for 24 hours to obtain the flocculant.

[0066] Comparative Example 2

[0067] A method for preparing a magnetized hydrophobic chitosan flocculant is basically the same as that of Example 1, except that there is no step (10), and the magnetized hydrophobic chitosan solution obtained in step (9) is directly left to stand and mature for 24 hours to obtain the flocculant.

[0068] Comparative Example 3

[0069] A method for preparing a hydrophobic chitosan-alum composite flocculant, which is substantially the same as that of Example 1, except that steps (6) to (8) are omitted.

[0070] Comparative Example 4

[0071] A method for preparing a magnetized chitosan-alum composite flocculant, which is substantially the same as Example 1, except that steps (1) to (5) are omitted, and the hydrophobic chitosan in step (6) is replaced by chitosan.

[0072] Effect verification

[0073] First, simulate wastewater to prepare experimental wastewater and then conduct corresponding effect verification. The steps for treating microplastics in wastewater are as follows: (1) adding the flocculants prepared in the above Examples 1 to 7 and Comparative Examples 1 to 4 to the wastewater containing microplastics; (2) stirring and coagulating; (3) flocculation; (4) precipitation; (5) using a magnet to adsorb flocs.

[0074] 1. Hydrophobicity of magnetized hydrophobic chitosan-alum composite flocculants prepared from chitosan and lauric acid at different molar mass ratios

[0075] In order to investigate the effect of different molar mass ratios of chitosan and lauric acid on the hydrophobicity of the prepared composite flocculant, the composite flocculants prepared in Examples 1 to 4 were tested respectively. The results are as follows. Figure 2 As shown, from Figure 2 It can be seen that, relative to chitosan, adding lauric acid to chitosan can improve the hydrophobicity of chitosan, and when the molar mass of chitosan remains unchanged, with the increase of the molar mass of lauric acid, the contact angle first increases and then decreases, wherein, when the molar mass ratio of chitosan to lauric acid is 1:1, the contact angle reaches a maximum value of 126.17°, indicating that the magnetized hydrophobic chitosan-alum composite flocculant prepared by the present invention has good hydrophobicity.

[0076] 2. Removal effect of magnetic hydrophobic chitosan-alum composite flocculant prepared by different mass ratios of Al2(SO4)3·18H2O and K2SO4 on PE

[0077] The effect of adding different mass ratios of Al2(SO4)3·18H2O and K2SO4 to prepare the magnetized hydrophobic chitosan-alum composite flocculant on the removal of PE was investigated. First, simulated wastewater was artificially prepared and then the magnetized hydrophobic chitosan-alum composite flocculants prepared in Example 1, Example 5, Example 6 and Example 7 were added to the wastewater for detection. The specific steps are as follows:

[0078] First, artificially prepare simulated wastewater containing 100 mg / L polyethylene (PE) (other components and content indicators in the simulated wastewater are consistent with those in the wastewater, which belongs to conventional technology and will not be listed one by one here), adjust the pH of the simulated wastewater to 7.5±0.1, place the simulated wastewater in a constant temperature oscillator at 25°C for 3 hours (to make the added substances uniform), and then place it in a stirrer (JJ-1A digital display power-enhancing electric stirrer) for coagulation experiment. First, turn at 300 rpm for 1 min, in order to make the solution mix evenly. Then add the magnetized hydrophobic chitosan-alum composite flocculant prepared in Example 1, Example 5, Example 6 and Example 7, stir rapidly at 400 rpm for 1 minute, stir slowly at 50 rpm for 15 minutes after the rapid stirring, and then precipitate for 60 minutes. At this time, the water sample becomes clear, and polyethylene is removed from the water body with the precipitation of flocs. After the precipitation is completed, the flocs are collected by an external magnetic field and weighed.

[0079] The results are as follows Figure 3 As shown, from Figure 3 It can be seen that when the mass of Al2(SO4)3·18H2O remains unchanged, the removal effect of PE increases with the increase of the mass of K2SO4. Among them, when the mass ratio of Al2(SO4)3·18H2O to K2SO4 is 1:3, the removal effect of PE is best, and the removal rate reaches 99.5%.

[0080] 3. Removal effect of different dosages of magnetic hydrophobic chitosan-alum composite flocculant on PE, PET, PP and PLA

[0081] Different amounts of the magnetized hydrophobic chitosan-alum composite flocculant prepared in Example 1 were added to the simulated wastewater to examine the removal effects of different amounts on different microplastics in the wastewater. The simulated wastewater used contained 100 mg / L polyethylene terephthalate (PET), 100 mg / L polyethylene (PE), 100 mg / L polylactic acid (PLA), and 100 mg / L polypropylene (PP), respectively, and the steps were the same as those in the above-mentioned effect verification part "II".

[0082] The results are as follows Figure 4 As shown, from Figure 4It can be seen that with the increase of dosage (25, 50, 75, 100, 125, 150ppm), the removal rates of PET, PE, PP and PLA are improved. Among them, when the dosage is 75ppm (75mg / L), the removal rates of PET, PE, PP and PLA reach 99.82%, 99.56%, 99.88% and 99.85% respectively, indicating that the magnetized hydrophobic chitosan-alum composite flocculant prepared by the present invention has a good removal effect on different types of microplastics, and a removal rate of 99% can be achieved when the dosage is 75mg / L, indicating that a good removal effect can be achieved with a small dosage.

[0083] 4. Removal effect of magnetized hydrophobic chitosan-alum composite flocculant on PE, PET, PP and PLA at different temperatures

[0084] In order to investigate the effect of temperature on the removal effect, the temperature was set as a variable (10°C, 25°C, 40°C), and the magnetized hydrophobic chitosan-alum composite flocculant prepared in Example 1 was added to the wastewater for investigation. The amount of addition was 75 mg / L, and then the temperature variable of the simulated wastewater was changed. The simulated wastewater was the same as the simulated wastewater in the "third" part of the above-mentioned effect verification, and the steps were the same as the steps in the "second" part of the above-mentioned effect verification. The removal rates of various types of microplastics in the wastewater at different temperatures were determined. The results are as follows: Figure 5 shown.

[0085] from Figure 5 It can be seen that with the increase of temperature, the overall impact on the removal rate is small, and the fluctuation value is less than 0.1%, indicating that temperature has little effect on the removal effect of flocculants. In wastewater at different temperatures, the flocculant has a good removal effect on microplastics.

[0086] 5. Removal effect of magnetized hydrophobic chitosan-alum composite flocculant on PE, PET, PP and PLA at different pH

[0087] In order to investigate the effect of pH on the removal effect, pH was set as a variable (5, 6, 7, 8, 9, 10), and the magnetized hydrophobic chitosan-alum composite flocculant prepared in Example 1 was added to the wastewater for investigation. The amount of addition was 75 mg / L, and then the pH variable of the simulated wastewater was changed. The simulated wastewater was the same as the simulated wastewater in the "third" part of the above-mentioned effect verification, and the steps were the same as the steps in the "second" part of the above-mentioned effect verification. The removal rates of various types of microplastics in wastewaters with different pH values ​​were determined. The results are as follows: Figure 6 shown.

[0088] from Figure 6It can be seen that it has a good removal effect in wastewater with a pH of 5-10. Among them, with the increase of pH, the removal first shows an upward and then downward trend. When the pH is about 7.2, the removal rate reaches 99%. Among them, when the pH is 7-9, the removal rate of all microplastics (PE, PET, PP, PLA) reaches more than 95%.

[0089] VI. Effect of different amounts of flocculants prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 on the removal of PE

[0090] In order to investigate the removal effect of microplastics (PE) in wastewater by Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 at the same dosage, different amounts of flocculants prepared by Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were added to the simulated wastewater (the simulated wastewater was the same as the simulated wastewater artificially prepared in the "second" part of the above effect verification). The results are as follows Figure 7 As shown. Figure 7 In the embodiment, HCs-alum is a hydrophobic chitosan-alum composite flocculant (Comparative Example 3), MCs-alum is a magnetized chitosan-alum composite flocculant (Comparative Example 4), MHCs-alum is a magnetized hydrophobic chitosan-alum composite flocculant (Example 1), HCs is a hydrophobic chitosan flocculant (Comparative Example 1), and MHCs is a magnetized hydrophobic chitosan flocculant (Comparative Example 2).

[0091] from Figure 7 It can be seen that the chitosan flocculant HCs after only hydrophobicization has a certain removal effect, but the overall removal rate is below 55%. Compared with HCs, MHCs, HCs-alum, and MCs-alum, the removal rate of MHCs-alum prepared by the present invention at different dosages is higher. Among them, when the dosage is 75 mg / L, the removal rate of MHCs-alum reaches 99%, while the removal rates of the other flocculants are lower than 90%. Compared with MHCs not compounded with alum, when the dosage is 75 mg / L, its removal rate is 65%, which is 34% different from MHCs-alum, indicating that the removal effect of MHCs-alum after compounding with alum is better, and the removal rate of MHCs can be improved after compounding with alum, so that the removal rate is significantly improved.

[0092] When the dosage of HCs-alum and MCs-alum was 75 mg / L, the removal rates were close, about 85%, indicating that when chitosan was modified by hydrophobicity or magnetization alone and then compounded with alum, the removal rate was greater than that of MHCs and HCs not compounded with alum, but less than the removal rate of MHCs-alum, indicating that when chitosan was modified by a single treatment (hydrophobicity or magnetization) and then compounded with alum, the removal effect was not better than that of chitosan modified by two treatments (hydrophobicity and magnetization) and then compounded with alum. The maximum difference in removal rate was about 14% (the dosage was 75 mg / L).

[0093] 7. Effect of different composite flocculants and different dosages on PE removal

[0094] In order to investigate the removal effect of the composites obtained by combining magnetized hydrophobic chitosan with different flocculants (inorganic and organic flocculants) on microplastics (PE) in wastewater at the same dosage, different amounts of different types of composites were added to the simulated wastewater (the simulated wastewater was the same as the artificially prepared simulated wastewater in the "second" part of the above effect verification). The removal effect of the composites on microplastics (PE) in the wastewater was as follows: Figure 8 As shown. Figure 8 In the embodiment, MHCs-alum is a magnetized hydrophobic chitosan-alum composite flocculant (prepared in Example 1), MHCs-FeCl3 is a magnetized hydrophobic chitosan-ferric chloride composite flocculant, MHCs-AlCl3 is a magnetized hydrophobic chitosan-aluminum chloride composite flocculant, and MHCs-starch is a magnetized hydrophobic chitosan-starch composite flocculant.

[0095] from Figure 8 It can be seen that the composite flocculant obtained by compounding magnetized hydrophobic chitosan (MHCs) with inorganic flocculants (alum, FeCl3, AlCl3) has a better removal effect on microplastics (PE) than the composite flocculant obtained by compounding with organic flocculants (starch); and when compounded with inorganic flocculants, the removal rate after compounding with alum is higher than that after compounding with iron salt (FeCl3) and aluminum salt (AlCl3) inorganic flocculants. Among them, when the dosage is 75 mg / L, the removal rate of MHCs-alum after compounding with alum reaches 99%, while the removal rate of MHCs-FeCl3 is about 76%, which is about 23% different from the removal rate of MHCs-alum, and the removal rate of MHCs-AlCl3 is about 79%, which is about 20% different from the removal rate of MHCs-alum, indicating that the effect after compounding with alum is the best.

[0096] Although the present invention has been described using the above preferred embodiments, it is not intended to limit the scope of protection of the present invention. Any person skilled in the art who makes various changes and modifications to the above embodiments without departing from the spirit and scope of the present invention still fall within the scope of protection of the present invention.

Claims

1. A method for preparing a magnetized hydrophobic chitosan-alum composite flocculant, characterized in that: The preparation method comprises the following steps: (1) dissolving chitosan in acetic acid to obtain a chitosan solution, adding methanol to the chitosan solution, adjusting the pH of the solution after stirring, and obtaining an acidified chitosan solution; (2) preparing mother solutions of lauric acid, N-hydroxysuccinimide (NHS), and 1-ethyl (3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) respectively, taking solutions of lauric acid, N-hydroxysuccinimide (NHS), and 1-ethyl (3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) respectively, adding them to ethanol simultaneously and stirring, adding acidified chitosan solution during stirring to react, adjusting the pH of the reaction solution after the reaction, and obtaining hydrophobic chitosan powder by centrifugation, washing, drying, and grinding; (3) adding hydrophobic chitosan powder into water, stirring, and then adding Fe3O4 magnetic particles to mix to obtain a mixed solution, first adding cyclohexane, an emulsifier, and a surfactant into the mixed solution, stirring and mixing, and then adding glutaraldehyde to carry out a cross-linking reaction to obtain a magnetized hydrophobic chitosan solution, collecting the magnetized hydrophobic chitosan solution through an external magnetic field, and washing, drying, and grinding to obtain a magnetized hydrophobic chitosan powder; (4) dissolving the obtained magnetized hydrophobic chitosan powder in an acetic acid solution or a hydrochloric acid solution to obtain a magnetized hydrophobic chitosan solution, adding Al2(SO4)3·18H2O and K2SO4 to the magnetized hydrophobic chitosan solution for reaction, and allowing to stand and mature after the reaction to obtain a magnetized hydrophobic chitosan-alum composite flocculant.

2. The method for preparing the magnetized hydrophobic chitosan-alum composite flocculant according to claim 1, characterized in that: In the step (2), the molar ratio of chitosan to lauric acid is 1:(0.2-2).

3. The method for preparing the magnetized hydrophobic chitosan-alum composite flocculant according to claim 1, characterized in that: In the step (2), the molar ratio of lauric acid, N-hydroxysuccinimide (NHS), and 1-ethyl (3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) is 1:2:

2.

4. The method for preparing the magnetized hydrophobic chitosan-alum composite flocculant according to claim 1, characterized in that: In the step (3), the mass ratio of the hydrophobic chitosan powder to the Fe3O4 magnetic particles is 1:(0.5-3).

5. The method for preparing the magnetized hydrophobic chitosan-alum composite flocculant according to claim 1, characterized in that: In the step (3), the volume ratio of cyclohexane, emulsifier and surfactant is 150:1:

30.

6. The method for preparing the magnetized hydrophobic chitosan-alum composite flocculant according to claim 1, characterized in that: In the step (4), the mass ratio of Al2(SO4)3·18H2O to K2SO4 is 1:(1-4).

7. The method for preparing the magnetized hydrophobic chitosan-alum composite flocculant according to claim 1, characterized in that: In the step (1), before adding methanol to the chitosan solution, the chitosan solution is first placed in a storage box at 2 to 6° C. for 24 to 28 hours, and the pH of the chitosan solution is adjusted by 1% acetic acid, and the pH of the acidified chitosan solution is 4; In the step (2), lauric acid, N-hydroxysuccinimide (NHS), and 1-ethyl (3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) are added to ethanol and stirred for 2 to 4 hours, and the acidified chitosan solution is added for reaction for 24 to 28 hours. The reaction solution is first ultrasonicated for 10 to 15 minutes and then the pH value of the reaction solution is adjusted to 9. The reaction solution is then placed in a storage box at 2 to 6° C. and stored for 24 to 28 hours. The hydrophobic chitosan powder is then obtained by centrifugation, washing, drying, and grinding.

8. The method for preparing the magnetized hydrophobic chitosan-alum composite flocculant according to claim 1, characterized in that: In the step (3), the hydrophobic chitosan and the Fe3O4 magnetic particles are mixed for 12 to 15 hours, cyclohexane, an emulsifier and a surfactant are added to the mixture for stirring and mixing for 3 to 5 hours, glutaraldehyde is added for cross-linking reaction at 50° C. for 3 to 5 hours, and the drying time is 24 to 26 hours; In the step (4), Al2(SO4)3·18H2O and K2SO4 are added to the magnetized hydrophobic chitosan solution at a temperature of 50 to 80°C, and the reaction is carried out at a rotation speed of 600 to 750 r / min for 3 to 5 hours, and the standing and aging time is 24 to 28 hours.

9. A magnetized hydrophobic chitosan-alum composite flocculant, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the magnetized hydrophobic chitosan-alum composite flocculant according to claim 9 in the treatment of wastewater containing microplastics.

Citation Information

Patent Citations

  • Hydrophobic chitosan-polyaluminum chloride (Hmcs-PAC) composite flocculant as well as preparation and application thereof

    CN115321657A

  • Magnetic response super-hydrophobic chitosan aerogel and application thereof in MPs adsorption and oil-water separation

    CN116983963A

  • Hydrophobic chitosan and hydrophobic chitosan fixed gel

    JP1995316201A